2017
DOI: 10.1371/journal.pone.0174106
|View full text |Cite
|
Sign up to set email alerts
|

A spontaneous mutation in kdsD, a biosynthesis gene for 3 Deoxy-D-manno-Octulosonic Acid, occurred in a ciprofloxacin resistant strain of Francisella tularensis and caused a high level of attenuation in murine models of tularemia

Abstract: Francisella tularensis, a gram–negative facultative intracellular bacterial pathogen, is the causative agent of tularemia and able to infect many mammalian species, including humans. Because of its ability to cause a lethal infection, low infectious dose, and aerosolizable nature, F. tularensis subspecies tularensis is considered a potential biowarfare agent. Due to its in vitro efficacy, ciprofloxacin is one of the antibiotics recommended for post-exposure prophylaxis of tularemia. In order to identify therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 104 publications
(112 reference statements)
3
10
0
Order By: Relevance
“…In agreement with the latter hypothesis, we observed that a highly FQ-resistant mutant of F. novicida (U112_Fno3) bearing a functionally-inert DNA gyrase mutation (GyrA_ΔE524, ΔS525) also had a nonsense mutation in FTN_0444 ( fupA ) [7]. Moreover, fupA was identified as one of seven mutated genes in a ciprofloxacin-resistant mutant of F. tularensis SCHU S4, alongside gyrA and parE [14].…”
Section: Introductionsupporting
confidence: 52%
“…In agreement with the latter hypothesis, we observed that a highly FQ-resistant mutant of F. novicida (U112_Fno3) bearing a functionally-inert DNA gyrase mutation (GyrA_ΔE524, ΔS525) also had a nonsense mutation in FTN_0444 ( fupA ) [7]. Moreover, fupA was identified as one of seven mutated genes in a ciprofloxacin-resistant mutant of F. tularensis SCHU S4, alongside gyrA and parE [14].…”
Section: Introductionsupporting
confidence: 52%
“…Therefore, LD 50 analysis was performed with all 10 strains by intranasal challenge of BALB/c mice ( Figure 7 and Table 4 ). As expected for both versions of Schu S4 (FRAN244 and FRAN249), and in agreement with previous results from our laboratory and others ( Chance et al, 2017 ), the LD 50 measurements for both versions were found to be <1 CFU.…”
Section: Resultssupporting
confidence: 93%
“…To assess the contribution of the slt gene to Francisella virulence, BALB/c mice were challenged via the intranasal route with various doses of either the WT strain or the slt mutant. As previously demonstrated, BALB/c mice were highly susceptible to challenge with the parent strain, and the LD 50 was calculated to be less than 1 CFU (Figure 7 and Table 2) (Chance et al, 2017). In contrast, the slt mutant was shown to be highly attenuated in the murine model, and a LD 50 value was not able to be measured as only 4/10 mice succumbed to infection at the highest challenge dose (620 CFU).…”
Section: Resultsmentioning
confidence: 52%
“…28 days post-vaccination, the three groups of Fn slt vaccinated mice and naïve control mice ( n = 20) were split into two groups of 10 and challenged intranasally with either a high (37 CFU) or low (6 CFU) dose of Ft Schu S4. Based upon our previous published data, the IN LD 50 for BALB/c mice is 1 CFU of Ft Schu S4 (Chance et al, 2017). However, despite the promising results with protection against Fn challenge, no protection was afforded to the mice receiving any dose of the slt mutant strain when challenged with the Ft Schu S4 strain (Figure 12).…”
Section: Resultsmentioning
confidence: 86%